ENGLISH LANGUAGE SKILLS AND EMPLOYMENT PROSPECTS IN THE TOURISM INDUSTRY - Dias, Naveen A. H (ShodhKosh: Journal of Visual and Performing Arts, 2024)
It is very evident that the tourism industry is vast and wide-ranging, diverse and exciting. A job in the tourism field can be adventurous, highly exciting and well paid also. Consequently, the job opportunities in the tourism industry are amongst the fastest growing in the world of employment. Fundamentally, the idea is that a degree in tourism management equips students on the fundamentals on sustainability, human resources, project management, and much more. The knowledge gained through a degree in this field will be useful for a variety of different careers.